PENGARUH LATIHAN RUBBER CORD SEATED ROW TERHADAP KEKUATAN OTOT LENGAN DAN BAHU SAAT MELAKUKAN SMASH PADA TIM BOLA VOLI PUTRA SMA BUDHI LUHUR PEKANBARU - Rizki Hidayat Putra Gultom; Slamet '; Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This research was aims to find out whether there is the effect of rubber cord seated row practice to the power of arm and shoulder muscle for men’svolleyball team of SMA Budhi Luhur Pekanbaru, so when doing SMAshing can be maximal. Type of this research is experimental, the population of this research was the men’s volleyball team of SMA Budhi Luhur Pekanbaru, and the sample was the total of population, which was 12 students. The instrument are conducted to determine the strength of the result of this research are expanding dynamometer. The data were analyzed by statistic to test normality by lilifors test in α0.05significant level.The hypothesis was the effect of rubber cord seated row practice to the power of arm and shoulder muscles.According analysis of t test, the result is Ttest is 12,46 and Ttabel 1,796, so Ttest>Ttabel. According statistic of analysis data, the average of pre-test is 22 and average of post-test is 25,83, so the data was normal. In conclusion, there was an effect of rubber cord seated row practice to the power of arm and shoulder muscle for men’s volleyball team of SMA Budhi Luhur Pekanbaru.Keyword : Rubber cord seated row, The power of arm and shoulder muscle